“I am strong in will but weak in action”: college English teachers’ research engagement in a Chinese regional university - Ni, Hui (Frontiers in Education, 2024)
Research incompetence has become a bottleneck hindering the professional development of many CETs (College English teachers) in China, and research on language teachers' research engagement needs to be enriched. The study explores the CETs' research engagement in the context of institutional performance evaluation reform at a Chinese non-key university. In-depth interviews of 6 practitioners show that the prospects of their research engagement are promising but restricted by many personal and contextual constraints. Their motivation to engage with/in research tends to be mainly external despite some gratifying internal drives. The symbiotic teaching-research nexus is not well maintained in practice, the research atmosphere needs improving, and competent research teams are expected to be established and well managed. The professional appraisal reform has initially enhanced the staff's research enthusiasm, but the boost may wear off due to its weak implementation. The university administration should offer essential resources and relevant support to teachers struggling in their academic careers. Moreover, teachers' agency to conduct research should be stimulated.